Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in a Dog in Connecticut in February 2021 - Dong-Hun Lee (MDPI AG, 2021)
We report the first detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a 3-month-old dog in Connecticut that died suddenly and was submitted to the state veterinary diagnostic laboratory for postmortem examination. Viral RNA was detected in multiple organs of the dog by reverse transcription real time-PCR (RT-qPCR). Negative and positive sense strands of viral RNA were visualized by in situ hybridization using RNAscope technology. Complete genome sequencing and phylogenetic analysis of the hCoV-19/USA/CT-CVMDL-Dog-1/2021 (CT_Dog/2021) virus were conducted to identify the origin and lineage of the virus. The CT_Dog/2021 virus belonged to the GH/B1.2. genetic lineage and was genetically similar to SARS-CoV-2 identified in humans in the U.S. during the winter of 2020–2021. However, it was not related to other SARS-CoV-2 variants identified from companion animals in the U.S. It contained both the D614G in spike and P323L in nsp12 substitutions, which have become the dominant mutations in the United States. The continued sporadic detections of SARS-CoV-2 in companion animals warrant public health concerns about the zoonotic potential of SARS-CoV-2 and enhance our collective understanding of the epidemiology of the virus.